2003
DOI: 10.1046/j.1475-097x.2003.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygenation responses to standing in elderly patients with predominantly diastolic dysfunction

Abstract: Patients with left ventricular dysfunction may have different orthostatic responses of blood pressure (BP) and cerebral oxygenation than healthy elderly subjects. We investigated orthostatic changes in systemic haemodynamic variables and cerebral oxygenation in 21 elderly patients with heart failure New York Heart Association class I-III in stable condition (age 70-83 years) after withdrawal of furosemide and captopril for 2 weeks, and in 18 healthy elderly subjects (age 70-84 years). Frontal cortical concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The lower SctO 2 among HF patients compared with controls, both at rest and during orthostatic provocation, supports the hypothesis of increased susceptibility to cerebral hypoperfusion during orthostatic stress in HF 9 . In contrast to the current study, NIRS performed on elderly patients with diastolic dysfunction during 10 min of standing revealed that HF patients exhibited a smaller decrease in SctO 2 compared with healthy elderly subjects 20 . The fact that the latter study required withdrawal of furosemide and captopril prior to tests, which may benefit the haemodynamic response to orthostasis, 21 may explain the conflicting results.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The lower SctO 2 among HF patients compared with controls, both at rest and during orthostatic provocation, supports the hypothesis of increased susceptibility to cerebral hypoperfusion during orthostatic stress in HF 9 . In contrast to the current study, NIRS performed on elderly patients with diastolic dysfunction during 10 min of standing revealed that HF patients exhibited a smaller decrease in SctO 2 compared with healthy elderly subjects 20 . The fact that the latter study required withdrawal of furosemide and captopril prior to tests, which may benefit the haemodynamic response to orthostasis, 21 may explain the conflicting results.…”
Section: Discussionsupporting
confidence: 56%
“…The fact that the latter study required withdrawal of furosemide and captopril prior to tests, which may benefit the haemodynamic response to orthostasis, 21 may explain the conflicting results. In addition, the latter study included patients with normal left ventricular EF 20 as opposed to the current study which included patients with both preserved, mid‐range, and reduced EF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this setting, modest hypotension or hypocapnia can accentuate brain hypoxic changes (Enlund et al, 1989;Hampson et al, 1990;Torella and McCollum, 2004). However, pathophysiological factors that may magnify this effect are unclear (Artru et al, 1998;Mehagnoul-Schipper et al, 2003). Recent studies suggest that patients with low baseline brain hemoglobin concentrations have a compromised ability to maintain an adequate brain oxygenation state during modest hypotension (Paisansathan et al, in press).…”
Section: Introductionmentioning
confidence: 99%